2011
DOI: 10.1504/ijbnn.2011.040997
|View full text |Cite
|
Sign up to set email alerts
|

Gold-carbon nanotube nanocomposites: synthesis and applications

Abstract: Nanocomposites are combinations of nanomaterials with other molecules or nanoscaled materials, such as nanoparticles or nanotubes. In general, these novel nanocomposites have different physical and chemical properties from the constituent particles or wires, and will thus allow new kinds of applications. Among these nanocomposites, gold-carbon nanotube (Au-CNT) composites are of particular interests, due to their easy fabrication protocols and broad potential applications. Au-CNT nanocomposites commonly refer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 129 publications
(159 reference statements)
0
27
0
Order By: Relevance
“…Surface-linked Au-CNT nanocomposites may further be classified as covalently linked and non-covalently linked (Zhang and Olin, 2011). For non-covalent bonding, there are several ways to attach linking molecules to carbon nanotubes, including p stacking (Chen et al, 2008;Liu et al, 2003;Wang et al, 2002, Wang and Bi, 2013Ou and Huang, 2006;Wang et al, 2007), hydrophobic forces (Richard et al, 2003;Cao et al, 2008;Xiao et al, 2008;Alexeyeva et al, 2006), and electrostatic interactions (Zhang and Olin, 2011;Jiang et al, 2003;Yao and Shiu, 2008). CNT/nanoparticle hybrid materials, in which nanoparticles are attached to CNT surfaces, have been reported to exhibit catalytic activity, enhanced electrical conductivity, and hydrogen-sensing capability, suggesting broad potential application in optoelectronics, molecular sensors and heterogeneous catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Surface-linked Au-CNT nanocomposites may further be classified as covalently linked and non-covalently linked (Zhang and Olin, 2011). For non-covalent bonding, there are several ways to attach linking molecules to carbon nanotubes, including p stacking (Chen et al, 2008;Liu et al, 2003;Wang et al, 2002, Wang and Bi, 2013Ou and Huang, 2006;Wang et al, 2007), hydrophobic forces (Richard et al, 2003;Cao et al, 2008;Xiao et al, 2008;Alexeyeva et al, 2006), and electrostatic interactions (Zhang and Olin, 2011;Jiang et al, 2003;Yao and Shiu, 2008). CNT/nanoparticle hybrid materials, in which nanoparticles are attached to CNT surfaces, have been reported to exhibit catalytic activity, enhanced electrical conductivity, and hydrogen-sensing capability, suggesting broad potential application in optoelectronics, molecular sensors and heterogeneous catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Among various nanocomposites, gold nanoparticles decorated carbon nanotubes (AuNPs/CNTs) have attracted a great deal of interest in diversified areas such as optical, chemical and biological sensing, electronic and catalytic applications [1][2][3][4][5][6][7][8][9][10] due to their combined outstanding properties and versatile syntheses. Based on the binding mode between AuNPs and CNTs, there have been three main approaches for the decoration of AuNPs on the surface of CNTs [11][12][13], including direct [14][15][16][17][18][19][20][21][22][23], covalent [24][25][26][27][28] and non-covalent [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] depositions. Nevertheless, some important drawbacks of the direct and the covalent attachments involving the ineffective size control of the former and the multistep reactions of the latter are still left to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Only when using CHCA matrix was the formation of some gold-containing compounds observed. However, careful analysis showed that, for example, the peaks that apparently corresponded to Au m C 12 + (m = 6, 8, [10][11][12][13][14][15][16][17][18][19][20] and Au m C 24 + (m = 5, 7, 9, 11) were actually isobaric adducts of Au m clusters with one or two units of a known CHCA matrix fragment ion with a mass of m/z 144. Investigation of the stoichiometry of selected clusters by MS n using argon as collision gas (as for gold content) confirmed that they were not gold carbides but isobaric gold-CHCA fragment complexes of unknown structure.…”
Section: Maldi Analysis Of Nd-ng Nano-compositementioning
confidence: 99%
“…[2,3] Gold nano-particles have been studied via laser desorption ionization time-of-flight mass spectrometry [4,5] and their use as a MALDI matrix for the ionization of various compounds has been evaluated. [4,6] Formation of NG composites with various carbonaceous materials such as graphene, [7][8][9][10] carbon nano-tubes, [11,12] fullerenes, [13,14] and their applications in various fields are known. For example, composites of gold nano-particles with carbon nano-tubes are widely applied in drug delivery, cancer imaging and disease detection.…”
mentioning
confidence: 99%
See 1 more Smart Citation